Experiences and views on SHS exposure prevention in Middle Eastern countries: a systematic review. (20th October 2021) - Hassanein, Z; Langley, T; Bogdanovica, I; Murray, R; Leonardi-Bee, J
Abstract: Background: More than 50% of non-smoking women and children are exposed to second-hand smoke (SHS) in Middle Eastern countries. This review aims to synthesize the evidence on experiences and views of parents, children, and professionals towards SHS exposure prevention in Middle Eastern countries. Methods: We included qualitative studies exploring experiences and views on prevention of SHS exposure among women and children in all settings in Middle Eastern countries. A systematic review was undertaken according to the Joanna Briggs Institute (JBI) guidelines for qualitative systematic reviews. Nine databases were searched from inception to January 2021. Meta-aggregation was used to synthesize the findings. Results: Out of 5229 records identified, two qualitative studies reported in three publications met the eligibility criteria and were included. Using the JBI checklist for qualitative research, the critical appraisal scores of all papers were high. One study was conducted in Turkey and the other one in Israel, and study participants were parents of children. A total of 49 findings were extracted and aggregated into 8 categories, based on the similarity of meaning. Parents were aware that SHS is harmful, although the hazards of SHS exposure were not commonly discussed during pregnancy. However, there were conflicting views on ways of SHS exposure and approaches to minimise it. Parents implemented rules to decrease SHS exposure among children. While some parents were uncertain about the effectiveness of protective measures. Most common perceived barriers to reducing SHS exposure were beliefs about traditional values and personal psychological factors. Conclusions: Parents in Middle Eastern countries knew that children's SHS exposure is harmful, though knowledge was not comprehensive and did not translate into actions to protect children. Health education program is essential to improve parental knowledge on hazards of SHS and effective preventive measures. Key messages: Parents' risk-awareness of SHS exposure is inadequate. Health education program is essential to improve parental knowledge on hazards of SHS and effective preventive measures in Middle Eastern countries.